Penyetelan Sudut Pantoskopik pada Frame Stainless Steel dengan Konstruksi Rimless Mounting - Zakaria Efendi; Wahyu Budiana; Murni Marlina Simarmata (Akademi Refraksi Optisi dan Optometry Gapopin, 2022)
Adjusting the pantoscopic angle on a stainless steel rimless mounting frame has a high risk, it requires the special skills of an Optimistic Refractionist and requires adequate and skilled equipment to use it, the right lens characteristics, and understanding of the technique for making adjustments. In this writing, the author uses a descriptive method from library data, one of which is by David S. McCleary entitled The Optician Training Manual. Adjusting the pantoscopic angle with the right technique on the stainless steel rimless mounting frame will avoid the risk of damage to the frame and lens, and can produce glasses that are comfortable to use by eyeglass wearers.